Farewell to Visual Studies - Frank, Gustav; Manghani, Sunil; Elkins, James, 1955- (Book collections on Project MUSE., 2015)
"A transdisciplinary collection of essays discussing the identity, nature, and future of visual studies as a laboratory for thinking about relations between fields including art history, cultural studies, sociology, visual anthropology, film studies, media studies, postcolonial studies, philosophy of history, the science of vision, and science studies"--Provided by publisher.